Rediscovering Mikola Husouski: Carmen De Statura Feritate Ac Venatione Bisontis In The Light Of Niccolo Machiavelli’s The Prince - Volha Korbut Salman (Selçuk Üniversitesi Sosyal Bilimler Enstitüsü Dergisi)
The dawn of the Renaissance saw the appearance of two literary masterpieces – The Prince by Niccolo Machiavelli in the Florenti ne Republic and Carmen de Statura Feritate ac Venatione Bisontis [The Song about the Bison, Its Stature, Ferocity and Hunt] by Mikola Husouski in the Grand Duchy of Lithuania. Nevertheless, the destiny that awaited the two works was fundamentally different. The Prince 1515 became the cornerstone of political science, providing the basis for the emergence of Machiavellianism, and its revolutionary and often extreme ideas and principles acquired universal acclaim. Carmen de Statura Feritate ac Venatione Bisontis [The Song about the Bison, Its Stature, Ferocity and Hunt] 1523 , in its turn, was soon forgotten and rediscovered only three centuries later, just recently becoming a masterpiece of the Belarusian and Slavic literature. It is through the symbol of the bison that the long poem celebrates the valour and noble free spirit of its native land, provides an image of an ideal ruler, glorifies the persona of Vytautas the Great – the ruler of the Grand Duchy of Lithuania, as well as acquaints the reader with the beauty of the state, which, at the time of the poem’s creation, was situated beyond the borders of the Holy Roman Empire, and was often regarded as a land of savages and barbarians, populated by fiends and ogres. The paper aims to trace the history of the poem, as well as to examine the attempt of Carmen de Statura Feritate ac Venatione Bisontis [The Song about the Bison, Its Stature, Ferocity and Hunt] to create an image of an ideal ruler and to glorify the valour of the native land. In addition, the paper analyses the significance of the poem in the retrospective of the major postulates introduced by its contemporary The Prince. It scrutinizes the similarities and differences with the revolutionary work, as well as highlights the overall importance of the poem for the Belarusian and Slavic literature